New Professional Profiles and Skills in the Journalistic Field: A Scoping Review and In-Depth Interviews with Professionals in Spain - Marques-Hayasaki, Paula; Roca-Cuberes, Carles; Singla Casellas, Carles (Brazilian journalism research, 2016)
The professional profiles and skills related to journalism are adapting to a new paradigm as a consequence of the advent of new technologies - the web 2.0, the end of the monopoly of news production by mass media, etc. This study aims to provide a comprehensive critical mapping of new professional profiles and skills demanded in the field of journalism, based on a scoping review and in-depth interviews with professionals and academics in Spain. The results show a great variety of new profiles and nomenclatures. This is in part because of a significant overlapping in the functions emphasized by them. With regards to skills, the traditional ones are still the most valued by the market, although new competencies are becoming more and more important.